Potential link between SARS-CoV-2 and Kawasaki disease: importance of dentists for the diagnosis - Hercílio Martelli Júnior; Renato Assis Machado; Daniella Reis Barbosa Martelli; Mauro Costa Barbosa; Paulo Rogério Ferreti Bonan; Ricardo Della Coletta (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract: Kawasaki disease (KD) is a vasculitis with predilection for coronary arteries. Due to a lack of reliable confirmatory laboratory tests, the diagnosis of KD is based on a characteristic pattern of clinical findings that appear in a typical temporal sequence. The diagnostic criteria have been periodically modified and the American Heart Association has proposed the most recent guidelines for its diagnosis. However, patients may have incomplete or atypical forms of KD and diagnosis can often be difficult. Because oropharyngeal manifestations are a common and important feature for diagnosing KD and recent studies have hypothesized a possible association between KD and the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), in this review we highlight the importance of dentists in the diagnosis of KD and its potential association with SARS-CoV-2.